UPAYA MENINGKATKAN MOTIVASI BELAJAR AKUTANSI MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA SISWA KELAS XII AKL DI SMK NEGERI 2 SELONG PADA SEMESTER GANJIL TAHUN AJARAN 2022/2023 - Hakim, Sukmanul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to increase the motivation to study Accounting in class XII AKL students using the Project Based Learning model at SMK Negeri 2 Selong in the academic year 2022/2023. This research is classroom action research (CAR). The subjects of this research were students in class XII AKL in the odd semester of the academic year 2022/2023, with a total of 22 students. This research was conducted in two cycles and at the end of each cycle an evaluation of student learning outcomes was carried out. Data collection techniques used simple observation and questionnaires. The research procedures included the stages of planning, implementing actions, observing and reflecting. The results showed that the effort to use the project-based learning model could increase the motivation of class XII AKL students. The increase in motivation was marked by increasing the average learning motivation for each cycle. In cycle I, the average cycle reached 73.71% increases to the number of students who did not complete 5 people and in cycle II decreased to 2 people. Thus, it can be concluded that the use of the project-based learning model can improve the learning outcomes of XII AKL students in the odd semester of the academic year 2022/2023.